The prospect of animated videos in agriculture and health: a case study in Benin - Bello-Bravo, Julia; Dannou, E.A.; Agunbiade, T.A.; Tamo, Manuele; Pittendrigh, Barry Robert (2013)
Cell-phone ready educational videos, translated into local languages, are a recent phenomenon in developing nations. One of the reasons for the emergence of this approach is due to the scarcity of other forms of educational materials with appropriate content for low literate learners. Additionally, the World Wide Web (WWW) has very little to offer in regards to audio-visual training materials that could be used to educate people in their own local languages without the need for literacy. Scientific Animations Without Borders (SAWBO) creates and works with local groups to deploy educational videos in local languages facilitating access to information and knowledge toindividuals in the developing world. This paper is based on a survey conducted with 83 individuals on the perception of three SAWBO educational animations - neem extracts for insect control, cholera and malaria prevention; and their potential as training tools for health and agricultural extension in Benin. These animations provide information and knowledge in a simple way, on complex ideas and techniques that could improve livelihoods. The results obtained in this studysuggest that animated videos are a well-received approach as a training tool in agriculture andprevention of diseases amongst populations with diverse literacy levels.